Pengungkapan Emosi Kekecewaan pada Anak Usia 1—3 Tahun: Sebuah Kajian Psikolinguistik - Elen Azmiati; NFN Nuryani (SUAR BETANG, 2021)
This study describes the expressions of disappointment in 1—3 years children in a psycholinguistic perspective. The purpose of this study is to identify, analyze, and describe the language or speech spoken by children when they expressing disappointment. The method used is descriptive qualitative analysis using the theory of children's language acquisition in the field of phonology and syntax. Conversation data is obtained naturally by recording events when children experience disappointment. The results of the analysis show that children tend to express expressions of disappointment through non-verbal language in the form of roaring, screaming, and crying accompanied by explanatory speech. At the phonological level, children first master vowel sounds and several consonant sounds, such as p, b, m, n, and h. At the syntactic level, children aged 1; 4 (1 year; 4 months) have just mastered verbs and nouns. Children aged 2; 0 is able to speak two words that fall into the category of verbs, nouns, pronouns, and negative expressions. Children aged 2: 9 are able to speak two or more words that fall into the noun, verb, adjective, or adverb category. AbstrakPenelitian ini memaparkan pengungkapan kekecewaan pada anak usia 1—3 tahun dari kacamata psikolinguistik. Tujuan penelitian ini untuk mengidentifikasi, menganalisis, dan mendeskripsikan bahasa atau tuturan yang dituturkan oleh anak-anak ketika dia mengalami kekecewaan. Metode yang digunakan adalah analisis kualitatif deskriptif dengan menggunakan teori pemerolehan bahasa anak dalam bidang fonologi dan sintaksis. Data percakapan diperoleh secara natural dengan cara merekam kejadiaan saat anak mengalami kekecewaan. Hasil analisis menunjukkan anak cenderung mengungkapkan ekspresi kekecewaan melalui bahasa nonverbal berupa raungan, teriakan, hingga tangisan yang disertai tuturan penjelas. Pada tataran Fonologi, anak lebih dahulu menguasai bunyi-bunyi vokal dan beberapa bunyi konsonan, seperti p, b, m, n, dan h. Pada tataran Sintaksis, anak usia 1; 4 (1 tahun; 4 bulan) baru menguasai verba dan nomina. Anak usia 2; 0 sudah mampu menuturkan dua kata yang masuk dalam kategori verba, nomina, pronomina, serta ungkapan negatif. Anak usia 2; 9 sudah mampu menuturkan dua atau lebih kata yang masuk kategori nomina, verba, adjektiva, atau adverbia.